Prevalence and risk factors of asymptomatic bacteriuria in community-dwelling Korean adults - Hyun Lee Ko; Soojin Lee; Dha Woon Im; Sung Woo Lee (PLoS ONE, 2026)
The clinical characteristics of asymptomatic bacteriuria (ASB) in community-dwelling Asian adults remain underexplored. We aimed to identify the potential risk factors for ASB in an Asian population. We conducted a cross-sectional analysis of 8,508 participants. Urinary bacteria were quantified using urine flow cytometry and semi-quantitatively reported on a scale from negative to 3 + . For this epidemiologic analysis, bacteriuria was operationally defined as a flow cytometry result of ≥1 + , rather than by culture-based criteria. ASB was defined as bacteriuria accompanied by a self-reported negative answer to the question: “Have you recently experienced any sudden and frequent need to urinate?” The overall prevalence of ASB was 4.6%, with rates of 5.9% in women and 1.0% in men under 50, and 9.5% in women and 1.6% in men over 50. Older age, women, and diabetes were associated with increased odds of having ASB, whereas high physical activity and serum albumin levels were associated with decreased odds. Regardless of age, diabetes status, and physical activity and serum albumin levels, women showed higher odds of ASB than did men. Men and women with high physical activity and serum albumin levels showed lower odds of ASB than those without high levels. Age, sex, diabetes, physical activity, and serum albumin levels were independently associated with ASB among community-dwelling Korean adults. Future studies need to confirm the potential beneficial association of high physical activity and serum albumin levels with ASB in men and women.